Gnotobiotic techniques - Trávnícek, J; Mandel, L (Folia microbiologica, 1979)
A brief review is given of the development of equipment used for rearing germfree animals in various laboratories and of our experience with designing germfree isolators and with the technology of rearing germfree piglets is presented. The philosophy of isolation as applied to the animal as a biological unit, the elimination of contamination and the theoretical prerequisites of isolation were considered by Reyniers (1943, 1959) and Trexler (1960).
Keywords: laboratorní zvířata; metody; krmivo pro zvířata; sterilizace; Animal Feed; gnotobiologické modely; Animals; Equipment and Supplies; Methods; Sterilization; Germ-Free Life; zvířata; Animals, Laboratory; prasata; Swine; zdravotnické prostředky